A silicon-membrane based artificial feeding system for Amblyomma sculptum nymphs - Obiegala, Anna (2025)
The aim of the study was to establish an artificial feeding system (AFS), based on silicon membranes, for Amblyomma sculptum nymphs and compare it to classical feeding systems using laboratory animals. Three cohorts of 60 nymphs were fed on a rabbit, calf, and with the newly established AFS using prewarmed (38 °C) defibrinated bovine blood. The attachment rate (38.3%) as well as the engorgement rate (36.7%) in the AFS were both significantly lower (p = 0.0001; p = 0.0002) than in the animal-based feeding systems (73.3–85%). Subsequent development of engorged nymphs was similar regarding engorgement weight (11.96–16.3 mg) and subsequent molting (78.3–100%) into adults in all three cohorts. The main limitations of the AFS are the low attachment and engorgement rates, which require further optimization to enhance initial attraction to the membrane, for instance, by adding external attractants to the membrane or stimulating agents such as ATP to the bovine blood. Despite these limitations, the developed AFS provides a valuable tool for future research on ticks, tick-borne diseases and drug efficacy.